2021
DOI: 10.1007/s11356-021-15044-5
|View full text |Cite
|
Sign up to set email alerts
|

The efficiency of CO2 market in the phase III EU ETS: analyzing in the context of a dynamic approach

Abstract: This study has investigated the changing efficiency for the phase III EU ETS CO 2 market using the daily historical data of allowance future prices and coverage from August 2015 to December 2020. We have applied two alternative tests for checking dependency by linear and nonlinear methods to achieve this goal, including generalized spectral (GS) and automatic portmanteau (AQ). Also, we had a comprehensive look at the carbon market evolution and the EU ETS scheme development over time. The analysis of observed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(3 citation statements)
references
References 44 publications
0
3
0
Order By: Relevance
“…The efficient-market hypothesis states that stock price reflects all of the information needed in making investment decisions. Mirzaee Ghazani and Jafari (2021) suggested that stock price may not reflect carbon emissions, hence an emission-trading system can help to detect the capacity to produce certainty in emissions reduction. Similarly, it is necessary to analyze whether carbon-emission efficiency is genuinely represented in stock price.…”
Section: Research Questionsmentioning
confidence: 99%
“…The efficient-market hypothesis states that stock price reflects all of the information needed in making investment decisions. Mirzaee Ghazani and Jafari (2021) suggested that stock price may not reflect carbon emissions, hence an emission-trading system can help to detect the capacity to produce certainty in emissions reduction. Similarly, it is necessary to analyze whether carbon-emission efficiency is genuinely represented in stock price.…”
Section: Research Questionsmentioning
confidence: 99%
“…Accordingly, a point of departure for testing the market efficiency should be the relationship between carbon spot and futures prices. Although some researches on Phase Ⅰ indeed follow this point (Daskalakis and Markellos, 2008;Chevallier, 2010;Joyeux and Milunovic, 2010), it is omitted by those on Phase Ⅱ and Ⅲ (Rittler, 2012;Charles et al, 2013;Tang et al, 2013;Stefan and Wellenreuther, 2020;Ghazani and Jafari, 2021). The latter mainly focus on the performance of certain carbon futures contracts but pay no attention to the two price series, thus severing the inherent link between the two prices and disregarding the original intention of establishing the EU carbon futures market.…”
Section: Introductionmentioning
confidence: 98%
“…How effectively the ETS integrates the costs of carbon emissions is an important critical dimension [6]. In this regard, a recent study showed a gradual improvement [7] due to the various corrective actions implemented over the years to reduce the risk of carbon leakage. This phenomenon implies that emission reductions within the EU could be offset by a concomitant increase in emissions, although elsewhere, due to the shift of production to places with more permissive regulations [8,9].…”
Section: Introductionmentioning
confidence: 99%